Impacts of vitamin A deficiency on biological rhythms: Insights from the literature - Guo, Xiangrong; Wang, Hui; Xu, Jian; Hua, Hui (Frontiers in Nutrition, 2022)
In addition to the important roles in vision, immune, and reproduction, vitamin A is essential in brain function. Previous studies have shown that retinoic acid (RA), the bioactive form of vitamin A, is involved in the regulation of various intracellular responses related to biological rhythms. RA is reported to affect circadian rhythm by binding to RA receptors, such as receptors in the circadian-feedback-loops in the mammalian suprachiasmatic-nucleus. However, evidence on the impacts of vitamin A deficiency (VAD) on biological rhythms is limited, and most of the related studies were conducted on animals. In this review, we describe the physiological functions of biological rhythms and physiological pathways/molecular mechanisms regulating the biological rhythms. We then discuss the current understanding of the associations of VAD with biological-rhythm disorders/diseases (sleep disorders, impairments in learning/memory, emotional disorders and other immune or metabolism diseases), and summarize the current proposed mechanisms (mainly by retinoid-nuclear-receptors and related proteins) for the associations. This review may help to recognize the role of VAD in biological rhythm disorders and stimulate clinical or epidemiological studies to confirm findings of related animal studies.